Más allá de lo económico: Los objetivos estratégicos de los TLCs de Chile y México; Beyond Economic Logic: The Strategic Goals of Chile's and Mexico's FTAs - Leslie Wehner (German Institute of Global and Area Studies (GIGA), 2008)
This article analyzes the 'other' goals that drive Chile and Mexico to achieve intra- and extra-regional FTAs. These countries have a predominantly economic motivation to negotiate FTAs. However, there are other elements that are less apparent, but equally important, in Chile's and Mexico's FTA policies. These accords can also be seen as means to power and as mechanisms for establishing a closer system of global economic governance than that available through multilateral forums. Therefore, these two countries' FTAs are an ad hoc system that represents their respective economic contexts and realities. In other words, FTAs as an essential part of Chile's and Mexico's foreign policies have a strategic political-economic logic that synthesizes the notions of power and institutions. However, these two forces do not exclude of the economic logic for FTAs, which focuses on the maximization of consumers' welfare and producers' gains. On the contrary, they have to be taken as complementary factors. – – In diesem Artikel werden die 'anderen' Ziele analysiert, die Chile und Mexiko dazu bewegen, intra- und extraregionale Freihandelsabkommen anzustreben. In diesen Staaten besteht ein vordringlicher ökonomischer Anreiz, Freihandelsabkommen abzuschließen. Nichtsdestoweniger gibt es weitere weniger offensichtliche, aber für die Gestaltung ihrer Freihandelspolitik gleichfalls bedeutsame Elemente. So können diese Vereinbarungen auch als Mittel zur Macht und als Mechanismen globaler ökonomischer Governance angesehen werden, die über die bereits in multilateralen Foren bestehenden hinausgehen. Die Freihandelsabkommen bilden in diesem Sinne ein Ad-hoc-System, das die jeweiligen ökonomischen und politischen Realitäten der beiden Länder repräsentiert. Das heißt, die Freihandelsabkommen haben als wesentlicher Bestandteil der chilenischen und der mexikanischen Außenpolitik eine strategische politisch-ökonomische Logik, die in der Vorstellung von Macht und Governance-Institutionen aufgeht. Diese beiden Kräfte stehen nicht im Widerspruch zur ökonomischen Logik der Freihandelsabkommen, deren Hauptanliegen die Maximierung des Wohles der Konsumenten und des Nutzens der Produzenten bildet, sondern sollten als komplementäre Faktoren angesehen werden.
Keywords: 300